ALOKASI ANGGARAN PENGADAAN ALAT TANGKAPPERIKANAN DAN IMPLIKASINYA TERHADAPPDRB SUB SEKTOR PERIKANANDI KABUPATEN KETAPANG - ME, H.MATJUNI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT The study entitled Allocation Budget Procurement of Fishing gear, fishpond and Implications forFisheries Subsector GRDP in Ketapang District, by Matjuni, Magister Program in Economics, University of Tanjungpura, aimed at testing the effect of giving aid fishing gear, fishponds aid to GRDP fisheries subsector in Ketapang District Fisheries Subsector. Using data disbursement of the aid fishing gear, pools and cages by the Department of Marine and Fisheries Ketapang and Fisheries Subsector GDP over five years from 2007 to 2011. Analysis using multiple linear regression models. The results of researc showed that 1) The provision of fishing gear to GRDP fisheries subsector negatively affect with regression coefficient of -3.253, meaning that if aid increases by one unit of fishing gear the fisheries sub-sector GDP fell by -3.253 units. However, based on the results of significance testing (t test) showed no significant results at the 95% confidence level (? = 0,05). 2) The provision of pool / cages positive effect on GRDP fisheries subsector with regression coefficient of 0.971 means an increase or decrease aid / cage of one unit will be followed by an increase or decrease in the same direction to GDP amounted to 0.971 units. The results show significant results in ? = 0.05. 3). F test results show together, aid gear, and ponds / cages do not significantly affect the fisheries sub-sector GRDP. Known of the value of F value = 7.689 value is smaller than F table and a significance greater than (? = 0.05) at 95% confidence level. Test results of determination (R2 = 0.885), meaning that 88.5% of independent variables (X1) and X2 (fishing gear) explained 88.5% of the dependent variable Y (GDP fisheries sub-sector), while the rest (11.5% influenced by variables Another unknown. Keywords: fisheries sub-sector of GRDP(Gross Regional Domestic Product), the aid fishing gear, help ponds, and cages.